An exploratory study on the publication stages of early access articles in different bibliographic databases: A case study of IEEE journals. - Yunu Zhu (PLoS ONE)
Currently bibliographic databases have included a large number of Early Access (EA) articles. Taking 47 IEEE journals as examples, this study analyzed and compared the differences in publication stages of EA articles in three typical bibliographic databases, including Web of Science Core Collection, Scopus, and Engineering Village Compendex. Qualitative analysis of data sets that may appear in these three databases and their publication stage modes, and quantitative analysis on the number of records, proportion, and journal distributions of each data set and each publication stage mode were conducted. There were totally 7 sub-data sets and corresponding 26 publication stage modes, with 14 "undifferentiated publication stage modes" and 12 "differentiated publication stage modes". Although the proportion of EA records from each "differentiated publication stage mode" was mostly below 1.0%, the absolute quantity of EA records with differences in the publication stage was noteworthy reaching 2516. Among the 47 journals, 23 journals have 7-8 publication stage modes, 1 journal having 18 modes, and 40 journals have one or more "differentiated publication stage modes". Therefore, in IEEE journals, whether for the same EA article or the same journal, the difference in publication stage between these three databases was pervasive and complex.